The Impact of Charter Schools on Catholic Schools: A Comparison of Programs in Arizona and Michigan - Ladner, Matthew (Catholic Education: A Journal of Inquiry and Practice, 2007)
Many Catholic educators assume that charter schools pose a significant threat to Catholic schools, especially in the urban core. Through an analysis of educational policy variations in Arizona and Michigan, this article demonstrates that while charter schools pose a threat to Catholic school enrollments, they do not always do so.